2001
DOI: 10.1038/sj.pcan.4500502
|View full text |Cite
|
Sign up to set email alerts
|

Defining a role for the inhibitors of apoptosis proteins in prostate cancer

Abstract: The aim of this paper is to review the inhibitors of apoptosis proteins, a recently discovered group of caspase inhibitors. We will brie¯y review the relevance of apoptosis in prostate cancer and some of the control mechanisms, before describing the structure, function and regulation of these molecules. Lastly, we will consider the evidence for the role that IAPs may have in cancer and the implications for prostate cancer in particular. Prostate Cancer and Prostatic Diseases (2001) 4, 28±32.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…XIAP is the most potent inhibitor of caspase activity. 70,71 High expression of IAPs in cancer cells can confer resistance to TRAIL-induced apoptosis.…”
Section: Bax and Bakmentioning
confidence: 99%
“…XIAP is the most potent inhibitor of caspase activity. 70,71 High expression of IAPs in cancer cells can confer resistance to TRAIL-induced apoptosis.…”
Section: Bax and Bakmentioning
confidence: 99%
“…Thus far, eight human IAPs have been identified including X-linked inhibitor of apoptosis protein (XIAP), inhibitor of apoptosis protein 1 (IAP1), inhibitor of apoptosis protein 2 (IAP2), and survivin (Krajewska et al, 2003). While they all appear capable of inhibiting effector caspases, IAP1 and IAP2 can directly and potently up-regulate NF-κB expression (McEleny et al, 2001). Elevated expression of all four IAPs has been shown in both animal models of prostate cancer and prostate tumors from patients undergoing prostatectomy, and this elevation appears to be present early in prostate cancer development (McEleny et al, 2001).…”
Section: Exploitation Of Apoptosis In Cancer Therapymentioning
confidence: 99%
“…While they all appear capable of inhibiting effector caspases, IAP1 and IAP2 can directly and potently up-regulate NF-κB expression (McEleny et al, 2001). Elevated expression of all four IAPs has been shown in both animal models of prostate cancer and prostate tumors from patients undergoing prostatectomy, and this elevation appears to be present early in prostate cancer development (McEleny et al, 2001). Indeed, recent evidence suggests that XIAP inhibition enhances chemotherapy sensitivity in otherwise resistant prostate cancer cell lines (Amantana et al, 2004).…”
Section: Exploitation Of Apoptosis In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…As to PCa, several studies identified that the survivin , though not normally expressed in the normal tissue and secretory epithelial cells of the prostate [24], was strongly expressed in PCa tissues and PCa cell lines at the level of RNA or protein [25-29]. Moreover, substantial evidence indicated that overexpression of survivin was related to the established features of biologically aggressive PCa, such as Gleason score and metastases [30-32].…”
Section: Introductionmentioning
confidence: 99%